2005
DOI: 10.1503/cmaj.050704
|View full text |Cite
|
Sign up to set email alerts
|

A new childhood pathway for transmission of an increased likelihood of smoking?

Abstract: CommentaireEven if the results of this study suggest prolonged waiting time does not worsen postoperative outcomes in padents with stenosis of the left main coronary artery, it remains essential to keep the waiting time short to reduce the risk while waiting and thus the total risk for padents accepted for CABG.Dr. Rexius is from the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 6 publications
1
12
0
Order By: Relevance
“…For instance, environments of tobacco smoke exposure are associated with increased smoking cues that may potentiate smoking behaviors among smokers (Field et al, 2007;McRobbie, Hajek, & Locker, 2008). Additionally, through the psychoactive effect of nicotine exposure from SHSe, novice smokers may be at increased susceptibility to initiate tobacco use (Anthonisen & Murray, 2005). Indeed, clinical studies have found that SHSe results in increased occupancy of nicotineacetylcholine receptors in the brains of adult smokers and nonsmokers, (Brody et al, 2011) suggesting increased neural vulnerability to nicotine exposure from SHS.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, environments of tobacco smoke exposure are associated with increased smoking cues that may potentiate smoking behaviors among smokers (Field et al, 2007;McRobbie, Hajek, & Locker, 2008). Additionally, through the psychoactive effect of nicotine exposure from SHSe, novice smokers may be at increased susceptibility to initiate tobacco use (Anthonisen & Murray, 2005). Indeed, clinical studies have found that SHSe results in increased occupancy of nicotineacetylcholine receptors in the brains of adult smokers and nonsmokers, (Brody et al, 2011) suggesting increased neural vulnerability to nicotine exposure from SHS.…”
Section: Introductionmentioning
confidence: 99%
“…Third, cumulative SHSe may change physiology [15] to increase risk for smoking initiation. Fourth, individual differences in sensitivity to SHSe, whether due to genetics or experience, may contribute to the relationship between SHSe and smoking initiation [16]. This paper tests the latter mechanism in a sample of high-risk 8-13 year-old preteens who have never smoked and who were living with a smoker in the home.…”
Section: Introductionmentioning
confidence: 99%
“…One mechanism that could account for the relationship between SHSe and smoking behavior is genetics, because children who live with parents who smoke likely have an inherited predisposition to smoking. [18][19][20][21] A second mechanism is individual differences in sensitivity to SHSe, 22 which could be influenced by genetic predisposition to smoking, genetic predisposition in sensitivity to SHSe, 23,24 by cumulative SHSe, by existing medical conditions, or a combination of these and other factors. A third mechanism is access to cigarettes and the modeling of smoking behavior to which exposed children are subject.…”
mentioning
confidence: 99%